Development of Flipbook Media for Producing Various Processed Products Made from Indramayu Mango to Improve Community Entrepreneurial Skills - Cahyana, Cucu; Artanti, Guspri Devi; Kandriasari, Annis; Yulianti, Yeni; Efrina, Efrina (Peneliti.net, 2025)
This study developed and evaluated a digital flipbook-based learning medium to enhance community entrepreneurial skills through the production of processed products made from Indramayu mangoes. The Research and Development (R&D) method, using the 4D model—Define, Design, Develop, and Disseminate—was employed. In the Define phase, needs were analysed through interviews and literature reviews to identify local entrepreneurial challenges. The Design phase involved creating media tools, including GBIM, material outlines, and storyboards, which were validated by experts. During the Develop phase, the flipbook was created using an application that integrated text, images, videos, and interactive links. Expert validation revealed high feasibility scores: 94% from subject matter experts, 90% from language experts, and 93% from media experts. In the Disseminate phase, trials with target communities were conducted. One-to-one, small group, and field tests demonstrated excellent suitability, scoring 92%, 91%, and 93%, respectively. Community feedback highlighted the media’s high usefulness and engagement. The findings indicate that the digital flipbook is a highly effective tool for enhancing entrepreneurial skills and utilizing local resources like Indramayu mangoes. It provides an engaging, accessible medium for learning and empowers communities to create innovative, marketable products.